Michael J. Walsh, Tamás Kiss and Nicholas S.H. Coureas (eds). The Harbour of all this Sea and Realm: Crusader to Venetian Famagusta - Carr, Mike (Journal of Greek Archaeology, 2017)
This volume derives from the editors’ desire to stimulate interest in the fascinating medieval town of Famagusta, located on the east coast of Cyprus, and to underpin the urgency in saving its valuable heritage. The book begins with a three-part multi-authored introduction by Michael Walsh, Tamás Kiss and Nicholas Coureas. Walsh’s section (pp. 3-8) highlights the precarious state of the walled city of Famagusta and the problems faced in preserving it. In 2008 it was placed on the international Watch List of Endangered Sites by the World Monuments Fund and the city remains ineligible to apply for UNESCO World Heritage Site status because of the current political situation.